Metabolic engineering of Bacillus subtilis for redistributing the carbon flux to 2,3-butanediol by manipulating NADH levels - Yang, Taowei (Biotechnol Biofuels, 2015)
BACKGROUND: Acetoin reductase (Acr) catalyzes the conversion of acetoin to 2,3-butanediol (2,3-BD) with concomitant oxidation of NADH to NAD(+). Therefore, intracellular 2,3-BD production is likely governed by the quantities of rate-limiting factor(s) Acr and/or NADH. Previously, we showed that a high level of Acr was beneficial for 2,3-BD accumulation. RESULTS: Metabolic engineering strategies were proposed to redistribute carbon flux to 2,3-BD by manipulating NADH levels. The disruption of NADH oxidase (YodC, encoded by yodC) by insertion of a formate dehydrogenase gene in Bacillussubtilis was more efficient for enhancing 2,3-BD production and decreasing acetoin formation than the disruption of YodC by the insertion of a Cat expression cassette. This was because the former resulted in the recombinant strain AFY in which an extra NADH regeneration system was introduced and NADH oxidase was disrupted simultaneously. On fermentation by strain AFY, the highest 2,3-BD concentration increased by 19.9 % while the acetoin titer decreased by 71.9 %, relative to the parental strain. However, the concentration of lactate, the main byproduct, increased by 47.2 %. To further improve carbon flux and NADH to 2,3-BD, the pathway to lactate was blocked using the insertional mutation technique to disrupt the lactate dehydrogenase gene ldhA. The resultant engineered strain B. subtilis AFYL could efficiently convert glucose into 2,3-BD with little acetoin and lactate accumulation. CONCLUSIONS: Through increasing the availability of NADH and decreasing the concentration of unwanted byproducts, this work demonstrates an important strategy in the metabolic engineering of 2,3-BD production by integrative recombinant hosts.